Real‐world oncological and toxicity outcomes with the Moscow strain of intravesical BCG for non‐muscle invasive bladder cancer—Implications for global shortage - Amandeep Arora; Sugam Godse; Mahendra Pal; Ankit Misra; Ravi Teja Sepuri; Naveen Thimiri Mallikarjun; Ajit Gujela; Sachin Patel; Anuj Sharma; Santosh Menon; Ganesh Bakshi; Gagan Prakash (BJUI Compass)
Abstract Objective This study aims to determine the oncological effectiveness and adverse‐effect profile of the Moscow strain of intravesical bacille Calmette–Guérin (BCG) for intermediate and high‐risk non‐muscle invasive bladder cancer (NMIBC). Materials and methods We performed a retrospective search of consecutive intermediate and high‐risk non‐muscle invasive bladder cancer patients who were started on intravesical BCG at 80 mg dose from January 2020 to December 2021. Data were collected for oncological outcomes and adverse effects of BCG. High‐grade recurrence‐free survival (HGRFS) was defined as any relapse of high‐grade (HG) urothelial cancer or carcinoma in situ (CIS). The primary outcome was to determine the HGRFS for those with originally HG disease. The RFS and HGRFS were calculated for the entire cohort, and also stratified by whether the patients had received adequate BCG or not. Results We identified 166 patients during the study period, of which 79.6% had HG disease. There were 25 recurrences (15.1%) in the entire cohort over a median follow‐up of 29 months. The RFS for the entire cohort at 12 and 24 months was 89.8% and 86.7%, respectively. For those with baseline HG disease, the 12‐ and 24‐month HG‐RFS was 90.9% and 87.1%. For the overall cohort, those who had received adequate BCG (n = 130, 78.3%) had a 12‐ and 24‐month RFS of 96.9% and 95.4%, which was significantly higher than those who were not able to receive adequate BCG (n = 31, 18.6%) (12‐ and 24‐month RFS of 74.2% and 64.5%), p < 0.001. Around 10% patients dropped out at each sequential maintenance phase, either because of BCG intolerance or because of failure to comply with the BCG instillation schedule. Severe side effects led to BCG discontinuation in 38.5% patients. Conclusion The Moscow strain BCG at 80 mg dose has excellent oncological outcomes, especially in patients who can take adequate BCG instillations, but BCG intolerance is a problem in a significant proportion of patients.